Adverse respiratory events after general anesthesia in patients at high risk of obstructive sleep apnea syndrome - Xará,Daniela (2015)
ABSTRACTINTRODUCTION: Patients with STOP-BANG score >3 have a high risk of Obstructive sleep apnea. The aim of this study was to evaluate early postoperative respiratory complications in adults with STOP-BANG score >3 after general anesthesia.METHODS: This is a prospective double cohort study matching 59 pairs of adult patients with STOP-BANG score >3 (high risk of obstructive sleep apnea) and patients with STOP-BANG score <3 (low risk of obstructive sleep apnea), similar with respect to gender, age and type of surgery, admitted after elective surgery in the Post-Anaesthesia Care Unit in May 2011. Primary outcome was the development of adverse respiratory events. Demographics data, perioperative variables, and postoperative length of stay in the Post-Anesthesia Care Unit and in hospital were recorded. The Mann-Whitney test, the chi-square test and the Fisher exact test were used for comparisons.RESULTS: Subjects in both pairs of study subjects had a median age of 56 years, including 25% males, and 59% were submitted to intra-abdominal surgery. High risk of obstructive sleep apnea patients had a higher median body mass index (31 versus 24 kg/m2, p < 0.001) and had more frequently co-morbidities, including hypertension (58% versus 24%, p < 0.001), dyslipidemia (46% versus 17%, p < 0.001) and insulin-treated diabetes mellitus (17% versus 2%, p = 0.004). These patients were submitted more frequently to bariatric surgery (20% versus 2%, p = 0.002). Patients with high risk of obstructive sleep apnea had more frequently adverse respiratory events (39% versus 10%, p < 0.001), mild to moderate desaturation (15% versus 0%, p = 0.001) and inability to breathe deeply (34% versus 9%, p = 0.001).CONCLUSION: After general anesthesia high risk of obstructive sleep apnea patients had an increased incidence of postoperative respiratory complications.